The Commodified Happiness: The Only Established Source of Meaning in Oscar Wilde’s The Happy Prince and The Nightingale and the Rose - Poorghorban Younes (Prague Journal of English Studies, 2022)
Oscar Wilde’s fairy tales are not as well-recognised as his novel or his dramatic works. This paper circles around two of his tales, The Happy Prince and The Nightingale and the Rose. Through a postmodernist outlook, this study postulates the vigorous diatribe of Wilde against the consumer culture which was dominant within Victorian society. Wilde asserts that the Victorian mind-set claims that happiness is attainable through accumulating signs of affluence and he ironically mocks this notion of happiness which is entitled to commodified objects. To him, happiness is defined through a strict sense of Christian morality and Christ-like love and kindness. His aesthetic views are entangled with morality and he fails to celebrate art for art’s sake. Moreover, this study asserts that Wilde is aware of the dominant language games, and his application of the technical language game for the Prince, the Nightingale, and the Swallow is in debt to his monolithic morality or his opportunistic character. At last, Wilde refuses to celebrate beauty if morality is absent and in this way, his aesthetic concerns become rather contradictory.